A Toolbox for Site-Specific Labeling of RecQ Helicase With a Single Fluorophore Used in the Single-Molecule Assay - Teng, Fang-Yuan; Jiang, Zong-Zhe; Huang, Ling-Yun; Guo, Man; Chen, Feng; Hou, Xi-Miao; Xi, Xu-Guang; Xu, Yong (Frontiers in Molecular Biosciences, 2020)
Fluorescently labeled proteins can improve the detection sensitivity and have been widely used in a variety of biological measurements. In single-molecule assays, site-specific labeling of proteins enables the visualization of molecular interactions, conformational changes in proteins, and enzymatic activity. In this study, based on a ﬂexible linker in the E. coli RecQ helicase, we established a scheme involving a combination of fluorophore labeling and Sortase A ligation to allow site-specific labeling of the HRDC domain of RecQ with a single Cy5 fluorophore, without inletting extra fluorescent domain or peptide fragment. Using single-molecule fluorescence resonance energy transfer (smFRET), we visualized that Cy5-labeled HRDC could directly interact with RecA domains and could bind to both the 3´ and 5´ ends of the overhang DNA dynamically in vitro for the first time. The present work not only reveals the functional mechanism of the HRDC domain, but also provides a feasible method for site-specific labeling of a domain with a single fluorophore used in single-molecule assays.